Development of Cabin Fever Scale in Malaysia - Chin Wen, Cong; Mohtaram, Rabbani (UNIMAS Publisher, 2021)
To prevent the spread of COVID-19, the Malaysian government implemented a movement control order, an emergency policy that instructed all people in the country to stay home. Being confined in a building for a lengthy period exposes individuals to the risk of having a range of symptoms known as cabin fever. Considering the negative impact of cabin fever, it is crucial to assess cabin fever symptoms among Malaysians. However, there is a lack of validated instruments; hence, this study attempts to develop an instrument for Malaysian adults, named Cabin Fever Scale (CFS). A total of 124 adults (75% females; M = 29.3 years) were recruited via the snowball sampling method to participate in an online survey. Exploratory factor analyses showed that the CFS items were pooled into two factors: behavioural symptoms (six items) and emotional symptoms (four items). Findings show that Malaysians viewed cabin fever as both behavioural and emotional symptoms. The behavioural symptoms comprise food craving, decreased motivation, difficulty waking up, and frequent naps, while emotional symptoms include anxiety, lethargy, depression, impatience, hopelessness, and dissatisfaction. Both CFS subscales demonstrated good internal reliability with Cronbach’s Alpha values of .768 (behavioural symptom) and .908 (emotional symptom). The 10-item CFS is deemed a psychometrically sound instrument for measuring cabin fever in Malaysia.